PENGARUH PERSEDIAAN BAHAN BAKU TERHADAP LABA BERSIH PERUSAHAAN PADA PT. YOKOGAWA INDONESIA - Djoko Maryanto (POLITEKNIK LP3I JAKARTA, 2020)
This research aims to determine the effect of the raw material inventory to net profit at PT. Yokogawa Indonesia. The value of raw material inventory that used to measure the effect on net profit is the value of Inventory-Work in Progress. The data used is a sample of the company's financial statements for 3 years (2011-2013). The method used in this thesis is a quantitative method to test the assumptions of classical, as well as statistical analysis of the simple linear regression analysis using SPSS version 20. The variable of this thesis is raw material inventory as a variable X (independent variable) and net profit as a variable Y (dependent variable), with a total sample for three years as many as 36 data. The result of this thesis is that Ho accepted raw materials inventory no significant effect on net income.Keywords: Raw Material Inventory, Net Profit, Inventory Work in Progress